Games contando histórias: uma discussão sobre a narrativa nos JRPGs - Picolo, Clarissa Marquezepi [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This paper is a consideration about narrative structure, narrator and narrative perspective in video games from a genre called JRPG. Starting from the idea that the games within this genre harmoniously combine narrative elements with ludic instances three games are analyzed, Chrono Trigger (2008), Tales of Symphonia (2004), Eternal Sonata (2009), which not only present mutual influence between narrative and rules, but also develop this combination to the point of providing different narrative pathways which can be activated and chosen according to the player. Hence, this thesis works with concepts from ludologists that searched for a definition of video games, such as Galloway (2006), Juul (2005) and Aarseth (2004); these concepts are discussed with ideas of narrative analysis, proposed by the narratologists Chatman (1978) and Bal (2007). The discussion then provides an understanding of the structure of a video game focusing on the organization of narrative elements along with with the ludic instances, the narrator present on this type of text, the narrative perspective by which events are narrated and the presence of the player as an effective participant in the development of the game. Supported by the convergence of those theoretical aspects, we shall draw up a proposal for a ludonarrative, a type of text in which stories are told by a narrator who lives and acts in accordance with the rules of the game, respecting them and giving meaning to them within the narrative, in order to significantly include the player not only as an interactor, but also as a participant in the text

O presente trabalho é uma reflexão sobre estrutura narrativa, narrador e foco narrativo em jogos eletrônicos do gênero JRPG. Partindo da ideia de que os jogos desse gênero combinam elementos narrativos com elementos lúdicos de forma harmônica, são analisados três títulos, Chrono Trigger (2008), Tales of Symphonia (2004), Eternal Sonata (2009), nos quais não só se verifica uma influência mútua entre narrativa e regras, mas que também desenvolvem essa união a ponto de apresentarem diferentes percursos narrativos que são ativados e escolhidos de acordo com o jogador. Dessa maneira, busca-se na ludologia as definições de jogos eletrônicos apresentadas por Galloway (2006), Juul (2005) e Aarseth (2004), que são postas a dialogar com conceitos da narratologia propostos por Chatman (1978) e Bal (2007), proporcionando o entendimento da estrutura de um jogo eletrônico em função da organização dos elementos narrativos em comunhão com os elementos lúdicos, do narrador presente neste tipo de texto, do foco narrativo pelo qual os eventos são narrados e da presença do jogador como um participante efetivo no desenvolvimento do jogo. Na convergência dessas duas vertentes teóricas, elabora-se uma proposta de ludonarrativa, espécie textual em que histórias são contadas por um narrador atuante, que vive e age de acordo com as regras do jogo, respeitando-as e dando sentido para elas dentro da narrativa, de modo a incluir significativamente o jogador não somente como um interagente, mas também como um participante no texto
Keywords: Literatura - História e critica - Teoria, etc; Análise do discurso narrativo; Narratologia; Ludologia; Jogos eletronicos; Discourse analysis, Narrative